The value of forgiveness to foster the culture of a healthy coexistence in Venezuela within the framework of peace and life. (Horizontes de Enfermería, 2018)
Education in Venezuela demands innovations every day due to the demands and differences that are presented in Venezuelan society. In this regard, the following action plan is presented: Exercising values through the practice of forgiveness as a means to foster the culture of a healthy coexistence in Venezuela in the framework of peace and life, a project that was organized to be executed in eight weeks That is, forty days. Through the Bolivarian curriculum, flexibility is allowed to build meaningful learn ing that goes to the benefit of a society. In this sense, the objectives of the research were raised, among them we have: To determine the importance of values through the practice of forgiveness as a means to foster the culture of a healthy coexistence in Venezuela within the framework of peace and life. The applied methodology was a qualitative investigation under the modality of the investigation participant action according to Pérez (1990). Taking as study space the National School, E.B. "Alfredo Pietri" de Boquerón, Carlos Arvelo Autonomous Municipality of the Carabobo-Venezuela State, the technique of participant observation and the interview to collect data was applied, as well as categorization and triangulation . A record of experience of the forty days was carried out, being of impact in the school, familiar and social scope.
Keywords: Values; Sorry; Culture; Healthy living togethe